Lactobacillus reuteri DSM 17938 effectively reduces the duration of acute diarrhoea in hospitalised children. (24th March 2014) - Dinleyici, Ener Cagri; PROBAGE Study Group; Vandenplas, Yvan; Dalgic, Nazan; Guven, Sirin; Metin, Özge; Eren, Makbule; Ozen, Metehan; Kara, Ates; Tanir, Gonul; Arica, Vefik; Sancar, Mesut; et al.
Abstract Aim Guidelines consider certain probiotics useful in the management of acute gastroenteritis. This study evaluated the use of Lactobacillus (L) reuteri DSM 17938. Methods A multicentre, randomised, single‐blind clinical trial was performed in hospitalised children with acute gastroenteritis lasting 12–72 h. Children received conventional therapy with, or without, 1 × 108 CFU of L. reuteri DSM 17938 for 5 days. The primary endpoint was the duration of diarrhoea and secondary outcomes were days of hospitalisation and the percentage of children with diarrhoea after each day of treatment. Results We compared 64 children receiving L. reuteri with 63 controls. Lactobacillus reuteri reduced the duration of diarrhoea after 24 h (p < 0.001) and more diarrhoea‐free children were seen in the L. reuteri than control group after 24 and 48 h (50% versus 5%, p < 0.001) and 72 h (69% versus 11%, p < 0.001). Lactobacillus reuteri reduced mean hospital stays (4.31 ± 1.3 days versus 5.46 ± 1.77 days, p < 0.001). Prolonged diarrhoea occurred in 17% of the controls, but none of the L. reuteri group. No adverse effects were reported. Conclusion Lactobacillus reuteri effectively reduced the duration of acute diarrhoea and hospital stays in children hospitalised with acute gastroenteritis. Outpatient data are now required.